Prolonged releasing gastroretentive drug delivery system using biopolymers - Nathanael, William (Nanyang Technological University, 2022)
Antiparkinsonian drugs, such as Entacapone, must be absorbed in the upper gastrointestinal tract, and thus a gastroretentive delivery system is required. There are many possible approaches to the gastro-retention problem, including expandable systems, bioadhesive systems, and magnetic systems, but this paper will focus on floating systems. This project aims to study the possibility of electrospinning zein, a natural polymer, to fabricate fibermesh to prolong the gastric residence time of the dosage form in gastric environments for more than a week. The fibermesh were combined with hydrogel rafts, and their combined retardation effects were investigated. The release rates of the dosage form will be conducted in vitro, using simulated gastric fluid under physiological temperature, and quantified using high-performance liquid chromatography (HPLC). SEM images show that zein/alginate fibers form only beaded fibers which are not ideal for drug delivery. Furthermore, good fibers can be formed by increasing the zein concentration to over 30%. The HPLC results show that the retardation effects from the zein fibermesh and hydrogel rafts can stack, and follow the first-order release kinetics. In conclusion, the zein fibermesh in tandem with hydrogel rafts is an effective approach to fabricate gastroretentive drug deliverys systems administering hydrophobic antiparkinsonian drugs.